Nitrogen-Containing Fabric Adsorbents Prepared by Radiation Grafting for Removal of Chromium from Wastewater - Natsuki Hayashi (Polymers, 2018)
To remove chromium from wastewater effectively, two types of nitrogen-containing fabric adsorbents, having amidoxime ligand groups and quaternary ammonium anion exchange groups, respectively, were prepared by radiation grafting. In brief, the amidoxime adsorbent is obtained by grafting of acrylonitrile (AN)/methacrylic acid (MAA) onto a nonwoven fabric and subsequent amidoximation with hydroxylamine, while the ammonium adsorbent is obtained by grafting of chloromethylstyrene (CMS) followed by quaternization with trimethylamine. The AN/MAA-grafting reaches a high degree of grafting more than 100%, and the resulting amidoxime adsorbent reaches a high amidoxime density of 4.53 mmol/g. On the other hand, the CMS-grafting reaches a much higher degree of grafting above 200%, and the resulting ammonium adsorbent reaches a high ammonium density of 3.51 mmol/g. FTIR/ATR and TGA/DTA are used for the characterization of the grafted fabrics as well as the relevant fabric adsorbents. Furthermore, the chromium removal of the prepared fabric adsorbent is tested in both batch and column modes. It has been confirmed that the chromium removal was largely dependent on the pH of the solution. At pH 5.0, the amidoxime adsorbent shows a high Cr(III) adsorption capacity of 31.68 mg/g, while the ammonium adsorbent shows a much higher Cr(VI) adsorption capacity of 130.65 mg/g.